URBAN MOBILITY IN POST-COVID CITY: Assessing the Conflict between Safe and Sustainable Urban Mobility in Four Types of Neighbourhoods in GCR Egypt. - Islam Ghonimi (Journal of Architecture, Art & Humanistic Science, 2024)
Covid19 pandemic gives social distance great concerns in contemporary cities especially the one related to safe urban mobility. People were asked to choose travel modes that maintain safe social distance to minimize the chance of infection while traveling safely from place to another. Accordingly, urban mobility witnessed a paradigm shift from the first sustainable urban mobility paradigm that found efficiency in mass transportation and minimizing the need for extended private motorized mobility inside cities, to the new safe urban mobility paradigm that strive for reducing the face-to-face contact by encouraging single ride mobility. Accordingly, Planners are required to shift to the new paradigm of urban mobility, and scholars are required to question health safety of the new paradigm of urban mobility at the same time to question its sustainability. The research aims to compare adopted movement behaviour across different neighbourhood models including purpose of mobility, mode choices, trip distance, and trip frequency. The paper reports, based on empirical findings, to three conclusions. Firstly, covid19 caused different levels of coping movement behavioural change across different types of neighbourhoods. Secondly, the paper observed coping ideas of reducing unnecessary trips, displace mobility from public to private modes, distribution of trips to different times of the day, providing safe walkway for keeping social distance and encouraging walkability and cyclability. Finally, the paper deduced different design guidelines for urban form design that facilitate such coping urban mobility strategies and at the same time achieve sustainability including soft mixed use, soft density, and grid street patterns to facilitate coping of safe and sustainable urban mobility.